2020
DOI: 10.1002/eng2.12242
|View full text |Cite
|
Sign up to set email alerts
|

Factors implicating the validity and interpretation of mechanobiology studies in simulated microgravity environments

Abstract: Simulated microgravity (s-μg) devices provide unique conditions for elucidating the effects of gravitational unloading on biological processes and are increasingly being applied for mechanobiology studies. However, without proper characterization of the mechanical environment generated by these systems, the interpretation of results is confounded and limited. Furthermore, the cell culture approaches central to s-μg experimentation introduces new factors that can fundamentally affect results, but these are curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 143 publications
(247 reference statements)
0
11
0
Order By: Relevance
“…Our studies might have implications also in other contexts. Indeed simulating microgravity is becoming a useful tool to unveil the role of mechanical stimuli in health and disease ( Poon, 2020 ) and to optimize protocols for tissue engineering and regenerative medicine ( Grimm et al, 2018 ), thus answering the questions raised by Rinaldi (2016) about the meaning of space research.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies might have implications also in other contexts. Indeed simulating microgravity is becoming a useful tool to unveil the role of mechanical stimuli in health and disease ( Poon, 2020 ) and to optimize protocols for tissue engineering and regenerative medicine ( Grimm et al, 2018 ), thus answering the questions raised by Rinaldi (2016) about the meaning of space research.…”
Section: Discussionmentioning
confidence: 99%
“…To simulate reduced gravity, all experiments were carried out in the second generation of the software-driven Random Positioning Machine (RPM SW 2.0) (originally DutchSpace Airbus, Leiden, Netherlands, now Yuri GmbH, Meckenbeuren, Germany). The Mode of operation of this RPM differs from that of the earlier generation, which was developed for generating completely random paths, thus creating a simulated microgravity condition, and used for years in research 18 20 . The “mode of operation” of the RPM SW for simulating micro and partial gravity (see Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…While alternatives like parabolic flights exist for short-term studies, the experimental gold standards for simulating microgravity on Earth are rotating clinostats 16 or microgravity-simulating bioreactors 12 , 17 . There is ample evidence in the literature suggesting that the results of ground-based modeled microgravity studies mimic real space conditions 18 20 . In comparative studies, similar degrees of inhibition of proliferation and differentiation have been observed both in osteoblast-like cells cultured in true-microgravity in space as well as in experiments carried out in simulated microgravity using clinostats 21 .…”
Section: Introductionmentioning
confidence: 99%
“…The different means to simulate µ g on Earth is a source of heterogeneity in the studies analysing the effects of µ g on cancer cells. For a recent discussion of the different forces a cell is exposed in these devices, see the recent review by Poon [ 33 ].…”
Section: General Effects Of Microgravitymentioning
confidence: 99%